2012
DOI: 10.1111/j.1600-079x.2011.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes embryonic development and reduces reactive oxygen species in vitrified mouse 2‐cell embryos

Abstract: Two-cell embryos of mouse were vitrified by the open-pulled straw (OPS) method. The vitrified embryos were warmed and introduced into M16 medium for culture that contains melatonin at different concentrations (10(-3), 10(-5), 10(-7), 10(-9), 10(-11) m). This process caused reactive oxygen species (ROS) formation and jeopardized the development of the embryos. Melatonin, at different concentrations, significantly suppresses ROS production and promotes embryonic development in vitrified embryos compared with unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
110
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 54 publications
16
110
2
4
Order By: Relevance
“…It has been shown that intracellular GSH protects embryo from ROS [12]. Previous study has shown that the level of GSH decreased after vitrification and addition of melatonin increases the GSH levels [14]. The results of present study showed that the intracellular levels of GSH in 10 −9 and 10 −12 M groups were significantly improved relative to the control group.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…It has been shown that intracellular GSH protects embryo from ROS [12]. Previous study has shown that the level of GSH decreased after vitrification and addition of melatonin increases the GSH levels [14]. The results of present study showed that the intracellular levels of GSH in 10 −9 and 10 −12 M groups were significantly improved relative to the control group.…”
Section: Discussionsupporting
confidence: 73%
“…Ishizuka et al [21] suggested that the concentration of melatonin in mouse embryo development has a positive effect on 10 −6 M while Rodriguez-Osorio et al [15] claimed no significant difference in the cleavage stage of porcine embryo or blastocyst development in 10 −6 M concentration. Gao et al [14] vitrified two-cell mouse embryos obtained in vivo via OPS method, and found that melatonin at concentrations of 10 −5 to 10 −11 shows significant differences in the development of two-cell vitrified embryos to the blastocyst and increases the number of cells. Survival of frozen embryos is usually determined by growth in medium after warming.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations